‘In the weeds’: navigating the complex concerns, challenges and choices associated with medicinal cannabis consumption for endometriosis - Justin Sinclair; Allie Eathorne; Hannah Adler; Amelia Mardon; Orit Holtzman; Jason Abbott; Jerome Sarris; Mike Armour (Reproduction and Fertility)
People with endometriosis report consuming cannabis to manage their symptoms. Given the range of differing legalities and access pathways across the world, this study aimed to investigate the drivers and barriers to cannabis use worldwide. An online, anonymous, cross-sectional survey was distributed internationally by endometriosis organisations and was open to anyone consuming cannabis for endometriosis symptoms. Survey questions included motivations for both starting and ongoing cannabis consumption, concerns over cannabis use, reasons for stopping cannabis, and communication of cannabis consumption with healthcare providers. Eight hundred and eighty-nine responses were collected across >10 countries. Illicit cannabis (56.7%) was the most common access pathway. 99% of respondents stated they would continue to use cannabis to manage their endometriosis-based symptoms, with 90% reporting they would recommend its use to a friend or relative with the disease. The most common motivation(s) for cannabis consumption were inadequate pain control (68.6%) and bothersome side effects of medications (56.3%). Similar motivations were reported for ongoing cannabis consumption, with concerns over dependence/addiction on pharmaceutical medications (43.9%) being another common motivation. Those using illicit cannabis were significantly less likely (P < 0.0001) to disclose their cannabis consumption to medical professionals. Cannabis was viewed as superior to pharmaceuticals both in terms of effectiveness and side-effect profile. Despite this, concerns around cost, breaking the law, judgement due to stigma, and current drug-driving laws were reported. Illicit usage and lack of medical oversight raise concerns over potential drug interactions or withdrawal effects due to reduction in pharmaceutical medications because of cannabis.